2016
DOI: 10.5713/ajas.16.0023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acid whey and freeze-dried cranberries on lipid oxidation and fatty acid composition of nitrite-/nitrate-free fermented sausage made from deer meat

Abstract: ObjectiveThis study evaluated the effect of acid whey and freeze-dried cranberries on the physicochemical characteristics, lipid oxidation and fatty acid composition of nitrite-free fermented sausage made from deer meat and pork fat. Antioxidant interactions between acid whey and cranberry compounds were also explored.MethodsFour formulations of fermented venison sausage were prepared: F1 (control), F2 (with 5% liquid acid whey), F3 (with 0.06% of freeze-dried cranberries), and F4 (with 5% liquid acid whey and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
2
15
1
5
Order By: Relevance
“…Very few studies have been published on the incorporation of YAW in value-added food products. In one application for fermented deer sausage production (Karwowska and Dolatowski, 2017), it was found that acid whey addition decreased lightness (L*) and redness (a*), probably due to the effect of acid whey on the browning of heme. Incorporation of YAW may have an effect on the color attributes of a final product, caused by either interaction with other ingredients or the reaction of YAW components to processing conditions.…”
Section: Consumer Response To a Ranch Dressing Prepared By Replacing mentioning
confidence: 99%
“…Very few studies have been published on the incorporation of YAW in value-added food products. In one application for fermented deer sausage production (Karwowska and Dolatowski, 2017), it was found that acid whey addition decreased lightness (L*) and redness (a*), probably due to the effect of acid whey on the browning of heme. Incorporation of YAW may have an effect on the color attributes of a final product, caused by either interaction with other ingredients or the reaction of YAW components to processing conditions.…”
Section: Consumer Response To a Ranch Dressing Prepared By Replacing mentioning
confidence: 99%
“…However, in traditional technology, starter cultures are rarely used, and fermentation is accomplished by natural flora. Previous studies also indicate the possibility of using acid whey as a natural source of LAB [12][13][14][15]. The addition of acid whey in dry fermented sausage production improves its properties and enhances its nutritional value by acting on the heme iron content and fatty acid composition.…”
Section: Introductionmentioning
confidence: 99%
“…Berries are a great source of bioactive compounds, that act as strong antioxidants, being able to decrease the incidence of oxidative stress damage. [ 52 ] Karwowska and Dolatowski [ 18 ] reported that the acid whey combined with freeze‐dried cranberries could decrease the oxidative changes in sausages without nitrates. An improved stability of pork meat was achieved by feeding pigs with cranberry juice powder [ 22 ] ; it was reported a better oxidative stability of bacon and it was suggested that long term feeding can stabilize the pork products.…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 ] Berries leaves are by‐products of berries cultivation, meaning that large amounts of leaves are wasted annually. Previous research [ 2,5,7,11–29 ] showed a high phenolic content of leaves, similar to that of the fruits or even higher, indicating that they may be utilized as an alternative source of bioactive natural products.…”
Section: Introductionmentioning
confidence: 99%